Fluorescein Angiography of The Canine Ocular Fundus in Ketamine-Xylazine Anesthesia By - Kommonen, B. (Acta Vet Scand, 1984)
Fluorescein fundus angiography was performed on 30 dogs with no pathologic fundus findings using a Canon CF 60 Z wide angle camera. In serial photography of the dye passage 4 different circulatory phases could be distinguished: choroidal, retinal anteriolar, capillary and venous phase. The dye passage in the retinal vessels was described in detail. For aesthesia the combination of ketamine and xylazine proved to be suitable.